“Aplicación de programas de fertilización en el cultivo de arroz (Oryza sativa L.), bajo condiciones de riego, en la zona de Pimocha, Los Ríos.” - Gamboa Viva, Meibelin Lissbet (2019)
VIII. SUMMARY The present research work was carried out on the land owned by Mr. Miguel Bohórquez, located in the Province of Los Ríos, at Km. 6.5 of the Baba - Campo Alegre highway, with geographic coordinates UTM: X 9834140 - Y 666880. This area has a humid tropical climate, with an average annual temperature of 25.9 ° C, an annual rainfall of 2656 mm, relative humidity of 76%, evaporation of 1128 mm, heliophany of 3.5 hours of daylight and a height of 8 masl The rice variety INDIA SFL -11 was used as the sowing material. The treatments consisted of 6 fertilization programs of N-P-K-Mg-S-B-Zn; plus a control treatment with application of base fertilization. We used the experimental design Random Complete Blocks with seven treatments and 3 repetitions, the test of significance used was Tukey at 95% probability. All the necessary agricultural work was done in rice cultivation for its normal development as soil preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. To estimate the effects of the treatments, the following data were taken: plant height, number of tillers, number of panicles, length of panicles, grains per panicles, weight of 1000 grains, yield, partial productivity of nutrients, economic analysis. Based on the results obtained, it was determined that fertilization programs with treatments T1, T2, T3, T4, T5 and T6 were highly significant in height with respect to T7 (control). The treatment T5 with a dose of 138-0-90-0-0-0-0 (NPK-Mg-SB-Zn), presented higher number of tillers / m2 with 210.26, statistically superior to the T7 treatment (Control), with 93.86 tillers / m2. In the weight of 1000 grains, treatment 1 with a dose of 138-46-90-12-12-2-2, was greater than the rest of treatments with 15.30 g and numerically superior to treatment T7 (Control), with 9.94 g. The best performance we obtained was T1 at a dose 138-46-90-12-12-2-2, where 4902.47 kg / ha was reached, unlike the T7 treatment (Control), with 2360.49 Kg. Regarding the analysis economic, the fixed cost generated to produce one hectare of rice in this sector is $ 700, the greatest benefit was obtained by treatment 1, with a dose of 138-46-90-12-12-2-2 with $ 458.22. Key words: fertilization programs, yields, efficiency.